The Effect of Competence and Work Discipline on Teacher Performance at Madrasah Aliyah Negeri 1 Batang Hari - Zilawati Zilawati; Alfazri Rahmadani; M Andriansyah (P3M IAI Nusantara Batang Hari, 2021)
Based on the author's initial grand tour at Madrasah Aliyah Negeri 1 Batang Hari regarding the factors that affect teacher performance, including; competency factor that can be seen from the latest educational qualifications of teachers who are in accordance with the standards, but the number of certified teachers and teacher mastery of the subject matter taught is still not optimal. Then, the work discipline factor that can be seen from the level of teacher attendance in the last 3 months has increased and is good, but in terms of teacher obedience to Madrasa rules, it is still less/not optimal. In addition, teacher performance can also be influenced by the support given by the Madrasah Head to the teacher, which in this case is already optimal. Overall the teacher's performance achievement has been very good. The purpose of this study was to determine the effect of competence on teacher performance, to determine the effect of work discipline on teacher performance, and to determine the effect of competence and work discipline on teacher performance at Madrasah Aliyah Negeri 1 Batang Hari. The population in this study were teachers of Madrasah Aliyah Negeri 1 Batang Hari, while the research sample used a saturated sample where all members of the population were sampled as many as 29 teachers. The data analysis used was multiple linear regression analysis, and the data was processed with the help of the SPSS Version 20 program. The results showed that, partially competence has a significant effect on teacher performance by 46.1%. Work discipline has a significant effect on teacher performance by 39.7%. Simultaneously there is a significant influence between competence and work discipline on teacher performance of 80.3%, with the obtained value of fcount>ftable (53.093>3.37). This shows reject H0 and accept Ha. This means that there is a significant influence between competence and work discipline together (simultaneously) on the performance of teachers at Madrasah Aliyah Negeri 1 Batang Hari. Where if the competence and work discipline are getting better, the performance of teachers at Madrasah Aliyah Negeri 1 Batang Hari will also be better. While the remaining 19.7% is influenced by other variables not included in this study.